STUDENTS’ MOTIVATION FACTORS IN READING ENGLISH TEXTS AT ELESP BATCH 2021 - Rahmadina, Yulinda; Sutiono, Cayandrawati; Elyani, Eka Puteri (Universitas Putera Batam, 2023)
This study aims to find out dominant factors that play a role in students’ intrinsic and extrinsic motivation in reading English text Reading plays an essential role in language learning, particularly for EFL students. Students read English texts whether for academic purposes, gaining information, or for pleasure. To have excellent reading skills, students need to have the motivation to read various kinds of reading material. Motivation has long been identified as one of the main factors affecting English language learning. Some students are motivated to read in English intrinsically and extrinsically. This research is a quantitative descriptive study. The participants are 86 students of ELESP Lambung Mangkurat University Batch 2021. The researchers use total sampling because the total population is less than 100. A questionnaire is used as the instrument in this research. The result shows the factor that plays the most role in extrinsic motivation is grades and the lowest is social sharing. Meanwhile, the factor that plays the most role in intrinsic motivation is curiosity and the lowest is preference for challenge. Furthermore, students are found more motivated extrinsically in reading English rather than intrinsically motivated.